(untitled) (Acta Entomologica Serbica, 2019)
The Brachodidae family in Europe is represented only by the genus Brachodes, which has 14 species. So far, there has been no information on the presence of representatives of this family in Serbia. We found Brachodes pumila (Ochsenheimer, 1808) on Mount Stolovi in central Serbia. This is the first finding of B. pumila, genus Brachodes and family Brachodidae in Serbia.